PENGARUH KUALITAS HUBUNGAN SESAMA ANGGOTA TIM DAN KEPEMIMPINAN BERSAMA TERHADAP EFEKTIVITAS TIM PADA ORGANISASI PUBLIK - Anjar Ramdhana; Wustari L. Mangundjaya; Ahmad Cahyo Nugroho (Universitas Mercu Buana, 2018)
Abstract. This study aims to examine the effect of team member exchange qualities and shared leadership on team effectiveness in order to describe cross-functional integration conditions in public organizations. Cross-functional integration on these research explained with two points of view, as a group members behavior and as a team process. Cross-functional integration as a group members behavior established if (1) team member exchange qualities positively affects shared leadership; and (2) shared leadership positively affects team effectiveness. Cross-functional integration as a team process established if team member exchange qualities affects on team effectiveness through shared leadership. The study was conducted on Directorate A, B and C, with totally 90 respondents. The research method used regression analysis and path analysis. The results showed (1) team member exchange qualities positively affect shared leadership on Directorate A, B and C; (2) shared leadership positively affects team effectiveness on Directorate B and C; and (3) team member exchange qualities positively affects team effectiveness through shared leadership on Directorate C. Based on those results, we can conclude that cross-functional integration as group member behavior established in Directorate B and C, and cross-functional integration as a team process established only in Directorate C.